Prevention and Management of Healthcare-Associated Infections: Focus on Pneumonia and UTI - Abdullah Mana Mohammed Alqahtani, Khalid Ali Zaher Alzahiri, Saleh Hassan Ali, Abdullah Hassan Abdullah Awaji Alsaluli, Naif Hamoud Dh Alotaibi, Salman Bakhet Almutairi, Ghzeha othman ALotieby, Laila Ali Musaad Al shehri, Saleh Ahmad S Alebai (International Journal of Medical Toxicology and Legal Medicine, 2024)
Patients admitted to an acute care hospital or living in a long-term care facility have an increased risk of HAIs which usually include a wide range of infections involving different organs or systems, such as those affecting the lower respiratory tract, urinary tract, and bloodstream/vascular system. Rehabilitation units serve a specific segment of society, and patients include those at the highest risk for healthcare-associated illness, particularly those with chronic underlying illnesses, addictions, homelessness, immunosuppression, malignant diseases, prolonged hospitalizations, long-term endotracheal and intravenous catheters, chronic wounds, open fractures, and antimicrobial resistance. High vigilance for HAIs must be maintained, with adherence to guidelines and surveillance measures for prevention and early detection, in strict collaboration with the public health system, especially when a threatened outbreak of an antimicrobial-resistant strain is concerned. When HAIs are suspected, early multidisciplinary approaches are required, even as a catalyst to direct infection control measures. However, cautious use of broad-spectrum antimicrobials, early empirical treatments, and early diagnostics, with few but comprehensive invasive procedures, should be performed. Non-antimicrobial preventive therapies could be implemented for specific patient populations, but future alternatives for disease prevention, such as vaccines, monoclonal antibodies, and new chemical entities, will be available to clinicians.